VAKT Method in EFL Teaching Process: Does It Improve Students’ Reading Comprehension? - Firman Firman; Heri Hermawan; Hilda Hafid; Walhidayah Walhidayah (Ethical Lingua: Journal of Language Teaching and Literature, 2021)
Students must master the capacity to read comprehension because it is closely tied to their whole learning process and their ability to develop a broad perspective. Classroom Action Research was used in this study. The VAKT (Visual, Auditory, Kinaesthetic, and Tactile) method is used to increase students' reading comprehension skills. A diagnostic test to cycle I and cycle II (68.69 73.74 81.66) revealed that while students' average reading comprehension score was 68.69, after cycle I evaluation, their reading comprehension increased to 73.74, resulting in an increase in students' reading comprehension ability from the Diagnostic Test to cycle II of 81.66. and the results of previous research indicate that incorporating the VAKT learning approach (visual, auditory, kinaesthetic, and tactile) into the classroom can raise students' interest and motivation to improve their reading comprehension, as evidenced by the results display.